2002
DOI: 10.1080/00140130210127639
|View full text |Cite
|
Sign up to set email alerts
|

Effects of posture on dynamic back loading during a cable lifting task

Abstract: This study evaluated spinal loads associated with lifting and hanging heavy mining cable in a variety of postures. This electrical cable can weigh up to 10 kg per metre and is often lifted in restricted spaces in underground coal mines. Seven male subjects performed eight cable lifting and hanging tasks, while trunk kinematic data and trunk muscle electromyograms (EMGs) were obtained. The eight tasks were combinations of four postures (standing, stooping, kneeling on one knee, or kneeling on both knees) and tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Many authors have used HR rest as an indicator of physical workload related to muscular activities (38, 39). As the muscular activities are constant, so an increase in temperature in the summer months probably increases the HR rest and thus the overall workload of these female workers.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors have used HR rest as an indicator of physical workload related to muscular activities (38, 39). As the muscular activities are constant, so an increase in temperature in the summer months probably increases the HR rest and thus the overall workload of these female workers.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in muscle recruitment patterns were reported by Gallagher et al [10,11], who demonstrated that posture specific selective muscle recruitment occurs, independent of the load lifted, as individuals shift between standing, stooping, and kneeling on one or two knees. Squatting has been shown to reduce the activity of the lumbar erector spinae when compared to kneeling for a baggage handling task, while kneeling resulted in lower activity in the trapezius [46].…”
Section: Introductionmentioning
confidence: 87%
“…A recent study examined the influence of posture and load on the electromyographic activity of 10 trunk muscles during a heavy cable-lifting task (Gallagher, Marras, Davis, & Kovacs, 2002). Results of this study indicated that posture and load have quite different influences on trunk muscle recruitment (and thus loads experienced by the lumbar spine).…”
Section: Trunk Muscle Activity In Restricted Posturesmentioning
confidence: 95%